MODEL PEMBELAJARAN INTERAKTIF DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME UNTUK MENINGKATKAN PRESTASI BELAJAR FISIKA SISWA KELAS VIII SMP NEGERI 5 LINGSAR TAHUN PELAJARAN 2012/2013 - Sofian, Ifan (IKIP Mataram, 2013)
The facts found are that teacher’s use conventional learning, students only listen and record, Mid Semester Score has not reached the classical completion standard. Therefore this study aims to improve student physics learning achievement through the application of interactive learning model using constructivism approach on the students of class VIII SMP Negeri 5 Lingsar academic year 2012/2013. This research is a classroom action research that has been done in 2 cycles consisting of planning, implementation, observation, and reflection. Student questionnaire data given in cycle I through the questionnaire with an average score of 32.8 (positive category). Student achievement data obtained through the test given at each end of the cycle. Cycle I consists of 3 sessions. The results showed that the average score evaluation analysis 63.39 and classical learning completeness of 56.52% (category not complete). Cycle II consists of 4 sessions. The results show that the average score of evaluation analysis is 75.60 and the classical completeness is 86.95% (complete category). We conclude that the application of interactive learning model using constructivism approach has a positive impact on student physics achievement.